2019
DOI: 10.5999/aps.2018.00815
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic study of hand and upper extremity injuries by power tools

Abstract: Background Hand injuries caused by chain saws, electric saws, and hand grinders range from simple lacerations to tendon injuries, fractures, and even amputations. This study aimed to understand the distribution of various types of hand and upper extremity injuries caused by power tools, in order to help prevent them, by investigating the incidence and cause of power tool injuries treated over a 4-year period at a single institution in Korea. Methods We reviewed the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 15 publications
3
14
0
2
Order By: Relevance
“…Prior studies have characterized traumatic hand injuries often due to specific pieces of equipment; still, to the best of the authors' knowledge, no studies have comprehensively examined the current state of upper extremity injuries attributable to an entire class of appliances. 11,12 Our results suggest that, among the many mechanisms of injury associated with home-maintenance supplies, most injuries result from manual tools and saws. This aligns with previous research which also suggested that older saws were most likely to injury older individuals; namely, following CPSC regulations on saws, older adults became more likely to be affected.…”
Section: Discussionmentioning
confidence: 80%
“…Prior studies have characterized traumatic hand injuries often due to specific pieces of equipment; still, to the best of the authors' knowledge, no studies have comprehensively examined the current state of upper extremity injuries attributable to an entire class of appliances. 11,12 Our results suggest that, among the many mechanisms of injury associated with home-maintenance supplies, most injuries result from manual tools and saws. This aligns with previous research which also suggested that older saws were most likely to injury older individuals; namely, following CPSC regulations on saws, older adults became more likely to be affected.…”
Section: Discussionmentioning
confidence: 80%
“…Consistent with this study, open wounds have been found to be a leading FHW injury in the military and civilian populations. 5,27 In addition, previous studies found fractures accounted for a large proportion of FHW injuries in the USAF, other military agencies, and among civilians. 6,18,27,28 In addition, as we found in this study with females in the USAF, fractures have been found to be higher among those 55 years and older supporting the need for interventions specific to this group.…”
Section: Discussionmentioning
confidence: 97%
“…Compared with the US workforce age group of 35 to 44 years, workers aged 16 to 24 years had an incidence rate of FHW injuries that was 1.53 times higher. All other age groups in the US workforce (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54), and ≥55 years) had an incidence rate similar to the reference group (35-44 years). Among USAF personnel, males had an incidence rate of FHW injuries that was 1.63 times higher than females.…”
Section: Model-adjusted Rate Ratiosmentioning
confidence: 97%
“…Podríamos inferir que esto se debe a que en el hogar no utilizan las medidas de seguridad necesarias y que el nivel de expertise es menor que el de quienes se lesionan utilizando la herramienta para trabajar. Este dato se repite en la mayoría de los estudios publicados en la bibliografía, donde también la mayor parte de los accidentes se produce en el ámbito extralaboral (1)(2)(3)(4) .…”
Section: Discussionunclassified
“…En cuanto a las lesiones producidas, la gran mayoría ocurrió en los miembros superiores en el miembro no hábil, siendo más frecuentes en las manos, seguidas de las lesiones del antebrazo, lo que es consistente con la literatura (1,(3)(4)(5)(7)(8)(9)(10)(11) .…”
Section: Discussionunclassified